The role of some elicitors in inducing chilling stress resistance in apricot fruit - Ezzat, A.; Szabó, Zoltán; Ammar, A. K. (Acta Agraria Debreceniensis, 2014)
This study aimed to study the role of 2 mM salicylic acid and 0.2 mM methyl Jasmonic acid in reducing the chilling injuries on two different apricot varieties fruits (Bergarauge and Flavor cot). These treatments were applied for apricot fruit directly after harvest after measuring the zero time data. Then the fruit were stored at 1 oC for three weeks and were examined 7 day periodically, other group of fruit was stored at 1 oC for 15 days then transport to room temperature and examined after 4 and 8 days. The fruit samples were collected at each examination time, and the measurements containing the fruit firmness (Kg cm-2), chilling and decay index, membrane electrolyte leakage, total phenol content and phenylalanine ammonia lyase mechanism (PAL) activity. The results showed that there are no obvious differences between the tested varieties and the differences may back to genetic variations and they took the same trend for most of measurement after treated with SA and MJ. SA and/or MJ treated fruit achieved low percentage of fruit softening in comparison to water treated fruit. At the same time the chilling and decay index showed that the SA and/or MJ reduced the decay or breakdown symptoms in either tested varieties. The treated fruit with those elicitor help the fruit to keep about stable phenol content while water treated fruit lose the phenol content sharply at early storage and this stable level of phenol my because of the ability of those chemical to raise PAL activity in treated fruit.